PROBLEMS OF DEVELOPMENT OF TOURISM IN THE NORTH CAUCASUS AND NEW REALITIES IN THE THEORY OF TERRITORIAL RECREATIONAL SYSTEM - Victor Alexandrovich Shalnev; Anastasia Mihailovna Ignatenko; Svetlana Igorevna Savchenko (Вестник Северо-Кавказского федерального университета, 2022)
The active development of small and medium-sized tourism enterprises, their interaction and the formation of new structural units in the tourism sector requires new approaches in the theory of territorial recreational redun-dant system (TRS). The article describes the experience of learning new TRS and is considered the cluster model of tourism in the North Caucasus Federal District.